Towards excellence in disaster management: Governance and sustainability of post-disaster initiatives - Mishra, Pramod K. (2006)
Experience shows that post-disaster recovery and reconstruction provide - though one should not wait for a disaster to happen - an opportunity to introduce and enhance the acceptability of disaster risk reduction measures among various stakeholders. This, however, can be realised only if governance and sustainability issues are addressed. There is a need to create institutional structures and mechanisms to not only undertake disaster risk reduction measures, but also to incorporate them as an integral part of development programmes and schemes. It is also necessary to focus on pre-disaster planning for sustainable reconstruction and recovery. - Reproduced.
Keywords: Disaster prevention